PENGARUH WORK LIFE BALANCE, WORK ENGAGEMENT, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI MUSTIKARASA CAFE & RESTO GRESIK - Zahroh, Riris Amaliatus; Khasanah, Uswatun (Sekolah Tinggi Ilmu Ekonomi NU Trate Gresik, 2024)
This study aims to research the influence of work life balance, work engagement, and job satisfaction on employee performance at Mustikarasa Café & Resto Gresik. This study is a qualitative research that uses Partial Least Square (PLS) Structure Equation Modelling (SEM) analysis. The statistical tool used in this study is Warp-PLS. The respondents in this study were 52 employees who worked at Mustikarasa Café & Resto Gresik. The results of this study explain that work-life balance does not affect employee performance. In contrast to work engagement, it reduces employee performance and job satisfaction can improve employee performance at Mustikarasa café & resto Gresik.